Los romances de Lorenzo de Sepúlveda: de las ediciones antuerpienses a la "princeps" - Garvin, Mario (El Colegio de México, 2017)
Reception: November 14, 2016Accepted: February 20, 2017The two oldest preserved editions of the Romances of Lorenzo de Sepúlveda share a complex relationship. The common opinion is that Steelsio’s edition stems directly from the princeps while Nucio simply copies Steelsio. This paper argues that Nucio’s preserved editions actually derive from an older, lost edition of his own, which stems from the princeps and is also the source of Steelsio’s edition. If this is so, then it will be necessary to modify the bases determining the history of the so-called “Romancero erudite”, which begins with this work.